Piezoelectric coefficient of rice husk silica ceramics with BaTiO3 addition - Osman, Rosiah; Abdullah, Nor Hapishah; Md Yusof, Juraina; Hasan, Intan Helina (2018)
Piezoelectric coefficient (d33) will show the potential of a material to have piezoelectric properties. Once the piezoelectric properties of a material have been known, the application of that material will be easily determined. In this paper, study on piezoelectric coefficient for silica ceramic samples derived from Rice Husk Ash sintered at 1000ºC, 1100ºC and 1200ºC temperatures was done. BaTiO3 was added to enhance the piezoelectric d33 values in the Rice Husk. Characterization of piezoelectric coefficient (d33) of pure Rice Husk Ash, Rice Husk samples with 5wt% and 10wt% BaTiO3 addition were discussed. The value of d33 increases with increasing percentage of BaTiO3 addition.